Forecasting banknote circulation during the COVID-19 pandemic using structural time series models - Nikolaus Bartzsch; Marco Brandi; Raymond de Pastor; Lucas Devigne; Gianluca Maddaloni; Diana Posada Restrepo; Gabriele Sene (Deutsche Bundesbank, 2023)
As part of the Eurosystem's annual banknote production planning, the national central banks draw up forecasts estimating the volumes of national-issued banknotes in circulation for the three years ahead. As at the end of 2021, more than 80 per cent of euro banknotes in circulation (cumulated net issuance) had been issued by the national central banks of France, Germany, Italy and Spain ('4 NCBs'). To date, the 4 NCBs have been using ARIMAX models to forecast the banknotes issued nationally in circulation by denomination ('benchmark models'). This paper presents the structural time series models developed by the 4 NCBs as an additional forecasting tool. The forecast accuracy measures used in this study show that the structural time series models outperform the benchmark models currently in use at each of the 4 NCBs for most of the denominations. However, it should be borne in mind that the statistical informative value of this comparison is limited by the fact the projection period is only twelve months.
Keywords: C22; E41; E47; E51; 330; euro; demand for banknotes; forecast of banknotes in circulation; structural time series models; ARIMA models; intervention variables